Intelligent machining: a review of trends, achievements and current progress. Issue 4 (4th May 2022) - Imad, M.; Hopkins, C.; Hosseini, A.; Yussefian, N.Z.; Kishawy, H.A.
ABSTRACT: Manufacturing industries are constantly pressured by market demands to produce low-cost, high-quality products. Market demands tend to be complex and full of variations, especially in fast-paced industrial settings. To cope with the rising market demands, traditional manufacturing techniques are forced to develop and adapt advanced practices and methods. However, as advances in manufacturing technology grow, so does the need to implement them in an efficient and cost-effective manner. The outcome of this urgent need is a combination of traditional manufacturing tools and modern technologies, hardware or software, that transforms traditional manufacturing into intelligent manufacturing. Intelligent manufacturing systems are complex systems in which optimization methodologies are combined with sensor-based control systems. Such intelligent and optimized systems are capable of producing high-quality products at fast production rates and lower cost. Among the broad range of manufacturing processes, this paper focuses on machining and aims to detail the recent advances in the field of intelligent machining. The paper is divided into two interrelated topics, namely techniques and tools. Techniques are mainly referred to optimization techniques in intelligent machining while tools focus on smart cutting tools. The paper will detail the technological trends and significant contributions in each of these areas in chronological order.